INFLUENCE OF MATERNAL THYROID DYSFUNCTION ON PRETERM BIRTH - Abdurazakova, M.D.; Abduraxmanova , G.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
A frequent endocrine condition during pregnancy, thyroid dysfunction is becoming more well acknowledged as a risk factor for preterm delivery and poor neonatal outcomes. The physiological and pathological functions of thyroid hormones during pregnancy are examined in this review of the literature, with an emphasis on how they affect placentation, systemic inflammation, and uteroplacental hemodynamics. A higher risk of preterm labor, intrauterine growth restriction, and preeclampsia is linked to both overt and subclinical types of hypothyroidism and hyperthyroidism. Additionally, even in euthyroid women, thyroid autoantibodies and autoimmune thyroid disorders might make pregnancy health more difficult. This review emphasizes the significance of early diagnosis and tailored treatment by combining data from current research to clarify the pathways connecting thyroid dysfunction to unfavorable pregnancy outcomes.